Pengaruh Pemberian Ekstrak Andaliman (Zanthoxylumacanthopodium Dc.) Terhadap Jumlah Eritrosit Dan Hemoglobin Pada Tikus Putih (Rattus Norvegicus L.) Yang Di Induksi Boraks - Wiwik Sundari; Hafiza Hazmi; Mutiara Monica Pratiwi; Mutiara Ema; Rahmadani Sandra Nasution; Nurul Azmi; Abil Febriandi (LPPM Universitas Dharma Andalas, 2023)
Borax is a dangerous preservative and is not permitted for use in food. Borax can also interfere with metabolic enzymes. By utilizing herbal plants, namely by utilizing andaliman plants which contain terpenoids which have antioxidant and antimicrobial activity. This research method is experimental using a completely randomized design (CRD) with 16 male white rats with 4 treatment groups. The negative group was induced by distilled water for 14 days. positive control was induced by borax for 14 days, treatment groups 1 & 2 were induced by borax and andaliman extract for 14 days (P1=350 P2=400 mg/kg BW). The data obtained were tested using analysis of variance (ANOVA). The results of the one way ANOVA test on the observation of the number of erythrocytes showed a significant level of p = 0.00 which indicated that the induction of borax had a significant effect on the number of erythrocytes (p <0.05) and the results of the one way ANOVA test on the observation of the amount of hemoglobin showed a significant level of p = 0.047 which indicates that the induction of borax had a significant effect on the amount of hemoglobin (p <0.05).